Is thermography the most effective tool to monitor arthritis in rats? - DOĞAN, Elif; SEZER, Azizcan (Journal of Istanbul Veterinary Sciences, 2021)
In this study, it was aimed to compare the effect of clinical, radiological, and thermographic methods on the diagnosis and prognosis in experimentally rats with arthritis. A total of 24 rats were divided into 2 groups, each consisting of 12 rats. Arthritis was formed by administering 0,1 ml of FCA solution to the left-back extremities of the rats. The first group was called the control group. Cephalexin (60 mg/kg) and Diclofenac Sodium (1mg/kg) were applied to the second group to be the treatment group. From day 1 of the experiment, clinical evaluation and live weight measurements were performed every day. On the 7th, 14th, 21st, 28th days of the experiment, paw edema, radiographic, thermographic measurements were performed. While typical arthritis clinical findings obtain after FCA administration, no statistically significant difference was found when analyzing the changes of live weight measurements and paw edema measurements according to groups and time. The difference in the mean of the thermographic measurements of the arthritis-forming claws was statistically significant. Radiographically, degenerations in the joints and bones were found in the control group compared to the more in the treatment group. As a result, it was concluded that thermography can be a good alternative to clinical findings and radiography in the follow-up of arthritis.
Keywords: Veterinary Surgery; Inflammation of joint; monitoring; radiography; thermal camera; Veteriner Cerrahi; 3. Good health